Blockchain Adoption Challenges for SMEs: A Systematic Literature Review - Mukhlis Amien; Adnan Zulkarnain (J-INTECH ( Journal of Information and Technology), 2025)
Blockchain technology has emerged as a transformative force in various industries, with increasing interest from Small and Medium-sized Enterprises (SMEs). However, the adoption of blockchain by SMEs faces unique challenges that warrant comprehensive examination. This systematic literature review analyzes research on blockchain adoption challenges for SMEs published between 2019 and 2024. We reviewed 48 papers from major databases, including Scopus, Web of Science, and IEEE Xplore. Our analysis reveals three primary challenges: limited financial resources, lack of technical expertise, and regulatory uncertainty. The review also highlights a shift from conceptual to empirical studies over the period, indicating a maturing field of research. Geographically, 60% of studies focus on developing countries, particularly in Asia. Industry-wise, the supply chain sector dominates blockchain adoption research in SMEs (40%), followed by finance (25%) and manufacturing (20%). Despite challenges, significant benefits are identified, including enhanced supply chain transparency, improved operational efficiency, and better access to financing. This review contributes to the understanding of blockchain adoption in SMEs by synthesizing current knowledge, identifying research gaps, and proposing future research directions. Our findings provide valuable insights for researchers, practitioners, and policymakers involved infacilitating blockchain adoption among SMEs.